Design of non-reciprocal device based on magnetic photonic crystal fiber with enhanced birefringence. (June 2020) - Saker, Khadidja; Bouchemat, Touraya; Lahoubi, Mahieddine; Bouchemat, Mohamed; Pu, Shengli
Abstract: In this paper, a non-reciprocal device based on magnetic photonic crystal fiber of Yttrium iron garnet (YIG) is proposed. The unique magneto-optical (MO) properties of YIG are used to produce under the influence of a magnetic field parallel to the direction of propagation, a TE-TM mode conversion. The influence of gyrotropy on this latter, which depends on Faraday rotation, is analyzed. The structure parameters are simulated and the optimum efficiency of 93.57% is obtained. Faraday rotation and modal birefringence have been calculated by varying gyrotropy from 0.01 to 0.04. Compared to similar devices, the numerical results reveal an improvement of the MO properties, with an enhanced modal birefringence, which make it suitable for the design of MO isolators.